Structural characterization of vanadium oxide catalysts supported on nanostructured silica SBA-15 using X-ray absorption spectroscopy - Walter Anke; Herbert Rita; Hess Christian; Ressler Thorsten (Chemistry Central Journal, 2010)
Abstract The local structure of vanadium oxide supported on nanostructured SiO2 (VxOy/SBA-15) was investigated by in situ X-ray absorption spectroscopy (XAS). Because the number of potential parameters in XAS data analysis often exceeds the number of "independent" parameters, evaluating the reliability and significance of a particular fitting procedure is mandatory. The number of independent parameters (Nyquist) may not be sufficient. Hence, in addition to the number of independent parameters, a novel approach to evaluate the significance of structural fitting parameters in XAS data analysis is introduced. Three samples with different V loadings (i.e. 2.7 wt %, 5.4 wt %, and 10.8 wt %) were employed. Thermal treatment in air at 623 K resulted in characteristic structural changes of the V oxide species. Independent of the V loading, the local structure around V centers in dehydrated VxOy/SBA-15 corresponded to an ordered arrangement of adjacent V2O7 units. Moreover, the V2O7 units were found to persist under selective oxidation reaction conditions.